2013
DOI: 10.1021/jp400021u
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Bowing at Nanoscale: Investigation of CdSxSe1–x Alloy Quantum Dots through Cyclic Voltammetry and Density Functional Theory

Abstract: The band gap bowing effect in oleic acid-stabilized CdS x Se 1−x alloy quantum dots (Q-dots) with varying composition has been studied experimentally by means of cyclic voltammetry and theoretically using density functional theory based calculations. Distinct cathodic and anodic peaks observed in the cyclic voltammograms of diffusing quantum dots alloy are attributed to the respective conduction and valence band edges. The quasi-particle gap values determined from voltammetric measurements are compared with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…In short, electronic states of quantum dots can directly be invoked by these techniques. The band structure parameters of various quantum dots as a function of size [28] (size quantization effect) and composition [25] (band gap bowing effect) have been estimated by CV and matched very well with the independent results obtained by photoelectron spectroscopy in air (PESA) [25,36]. Interaction of graphene with quantum dots also have been studied and the results have been further corroborated by time resolved photoluminescence (PL) spectroscopy [29].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In short, electronic states of quantum dots can directly be invoked by these techniques. The band structure parameters of various quantum dots as a function of size [28] (size quantization effect) and composition [25] (band gap bowing effect) have been estimated by CV and matched very well with the independent results obtained by photoelectron spectroscopy in air (PESA) [25,36]. Interaction of graphene with quantum dots also have been studied and the results have been further corroborated by time resolved photoluminescence (PL) spectroscopy [29].…”
Section: Introductionsupporting
confidence: 69%
“…Both these techniques involve major instrumentation and tedious sample preparation and thus out of reach to many chemists for the routine applications. Recently, our group [25][26][27][28][29] and many others [30][31][32][33][34][35] have demonstrated that these parameters can equally accurately estimated by bench top approach like cyclic voltammetry (CV). Cathodic and anodic peaks in the CV analysis are associated to the electron transfer mediated through conduction and valence band-edges, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…E g(CdS) (2.50 eV) and E g(PbS) (0.41 eV) are the bulk bandgap energy of CdS and PbS, respectively. The corresponding literature values for the parameter b were reported to be very small for Pb chalcogenide alloys (0.03–0.09) and ≈0.45 for CdSe x S (1− x ) alloys . The calculated band gap energy as a function of Cd concentration in the shell is reported in Figure 7 in the Supporting Information for values of b in the range 0–0.5.…”
Section: Resultsmentioning
confidence: 95%
“…In ZnSe/CdS interfacial alloying with a fast cation diffusion and a relatively slower anion diffusion leads to a region at the core with a composition close to Zn x Cd 1 − x Se and an inner shell composed of Zn 1 − x Cd x S. As the alloyed materials have band edges between those of the pure, binary compounds a potential trough at the valence band edge is formed in the sulfur-rich region that further confines the 1S hole to the core [28]. This effect can be enhanced by band bowing, which causes the band edges to change non-linear with composition x [41][42][43]. The effect is more pronounced when the gradient involves two anions.…”
Section: Impact Of Random Phase Mixingmentioning
confidence: 99%